Analisis Kuantitatif Hubungan Kecerdasan Emosional dan Prestasi Akademik Siswa Sekolah Dasar - Marini Trianingsih; Mohamad Syarif Sumantri; Engga Dallion (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study aims to examine the relationship between emotional intelligence and academic achievement among elementary school students. The research was motivated by concerns about low academic performance and whether it is related to students' emotional intelligence levels. This quantitative correlational study involved 32 fifth-grade students from a public elementary school in East Jakarta. The instruments used included an emotional intelligence questionnaire and mid-semester examination scores as indicators of academic achievement. Validity and reliability tests were conducted to ensure instrument quality, followed by normality tests, linearity tests, and Pearson correlation analysis. The results using Spearman Rank correlation analysis showed a correlation coefficient of -0.098 with a significance level of 0.592 (> 0.05), indicating no significant relationship between emotional intelligence and academic achievement. These findings contribute to the scientific understanding that emotional intelligence is not the sole determinant of academic success and emphasize the need for comprehensive and contextual educational approaches in elementary education. The study suggests that other factors beyond emotional intelligence may play more crucial roles in determining academic performance among elementary school students, highlighting the complexity of factors influencing educational outcomes.